Epitaxial growth of ZnO on quartz substrate by sol-gel spin-coating method. (July 2016) - Chebil, W.; Boukadhaba, M.A.; Fouzri, A.
Abstract: ZnO thin films grown on Quartz substrates using sol–gel method were synthesized and annealing at different temperature (700 °C, 900 °C and 1000 °C). The structural, optical and morphological comparison of ZnO layers elaborated with that obtained by the sophisticated and expensive technique MOCVD demonstrates the success of the ZnO epitaxial growth on quartz substrate by sol-gel process. Sol-gel ZnO film deposited on quartz substrate annealed at 1000 °C exhibit only (00l) XRD peak which is similar to the diffraction patterns of epitaxial ZnO grown on sapphire by MOCVD. The Surface morphology was examined by SEM which revealed that the grain size becomes larger and faceted as increasing annealing temperature. Pl emission peak of sol-gel ZnO annealed at 1000 °C revealed a close similarity with that obtained by MOCVD ZnO but with a weaker intensity. Highlights: Success of the ZnO epitaxial growth on quartz substrate synthesised by sol-gel processes. Effect of temperature annealing on structural, optical and morphological of ZnO thin films were studied. Comparison of ZnO layers elaborated with that obtained by MOCVD demonstrates the obtaining of ZnO epitaxial growth by sol-gel processes.